2021
DOI: 10.3390/jcm10214861
|View full text |Cite
|
Sign up to set email alerts
|

Serum Calprotectin a Potential Biomarker in Juvenile Idiopathic Arthritis: A Meta-Analysis

Abstract: Juvenile idiopathic arthritis (JIA) is the most common inflammatory chronic disease affecting children and adolescents. Today, there are no specific biomarkers of inflammation. Therefore, it is important to identify new markers as predictors of disease activity. Recently, some researchers have directed their interest toward a protein, calprotectin (CLP), as a potential biomarker. The primary objective of our systematic review and meta-analysis was to analyze the possible role of CLP in JIA. Method: A literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
(76 reference statements)
1
7
1
Order By: Relevance
“…In this prospective longitudinal study, the first finding was that serum calprotectin levels, at baseline, were significantly higher in active patients than in controls and inactive patients, are were further increased with disease activity. In addition, we found that serum calprotectin values correlated strongly with JADAS27 and did not correlate with CRP, ESR, ANA and RF, nor with gender, age or disease duration of patients with JIA, partially in contrast with some previous reports [ 25 , 26 , 27 ]. In contrast with conventional markers of inflammation, which reflect the acute phase response mediated by hepatocytes or B lymphocytes during inflammation, calprotectin seems to provide additional information on the state of disease in JIA children.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In this prospective longitudinal study, the first finding was that serum calprotectin levels, at baseline, were significantly higher in active patients than in controls and inactive patients, are were further increased with disease activity. In addition, we found that serum calprotectin values correlated strongly with JADAS27 and did not correlate with CRP, ESR, ANA and RF, nor with gender, age or disease duration of patients with JIA, partially in contrast with some previous reports [ 25 , 26 , 27 ]. In contrast with conventional markers of inflammation, which reflect the acute phase response mediated by hepatocytes or B lymphocytes during inflammation, calprotectin seems to provide additional information on the state of disease in JIA children.…”
Section: Discussioncontrasting
confidence: 99%
“…A meta-analysis and systemic review was recently published including 10 specific studies on the pediatric population. Altobelli et al [ 27 ] confirmed that the use of serum calprotectin represents a useful tool in JIA in order to stratify disease activity in JIA children; however, the extreme heterogeneity of the JIA populations studied, especially in terms of treatment, did not allow further conclusive data. In addition, Hurnakova et al [ 28 ] showed that in RA patients, serum calprotectin was the best predictor of ultrasound synovitis, performing better than CRP.…”
Section: Discussionmentioning
confidence: 99%
“…However, it cannot be excluded that in vivo LDNs are primed and that they subsequently become more susceptible to other stimuli. JIA LDN percentage positively correlated with serum calprotectin levels, a potential marker for diagnosis, prediction of disease relapse, response to treatment and risk of flares in JIA and other autoimmune diseases, such as RA, SLE and inflammatory bowel disease ( 41 – 43 ). Calprotectin is released mostly by phagocyting cells such as neutrophils at the site of inflammation, where it can modulate inflammatory response ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Biomarkers were chosen based on reports of detection in serum and synovial fluid of JIA and RA patients. [20][21][22][23][24] S100 proteins, cytokine, and chemokine measurements were performed by the CCHMC Research Flow Cytometry Core. S100A8/A9 concentrations were determined by enzyme-linked immunosorbent assay using Pro-cartaPlex kits from ThermoFisher Scientific according to the manufacturer's directions.…”
Section: Significance and Innovationsmentioning
confidence: 99%